Ni positivismo jurídico ni neoconstitucionalismo: una defensa del constitucionalismo postpositivista - Atienza, Manuel (2017)
The process of founding constitutions in the legal systems of the Western world has generated an interesting debate; on the one hand, legal positivism (with its variants), which principally understands Law as a set of rules, whose most important attribute lies on the authority and the way it is expedited, totally detached from morality. On the other hand, the so-called “neoconstitutionalism”, which in total opposition to the previous one, sees the Law as a set of principles (recognized in the Constitution) whose application is purely evaluative and substantive, and therefore, requires morality in Law. Facing these antagonistic and to some extent unsustainable scenarios, postpositivist constitutionalism appears as an alternative. It conceives Law in a broader, more complete, and complex way, which includes descriptive, normative and value aspects, guiding the practice of the jurist in the context of a Constitutional State.